2018
DOI: 10.1021/acs.est.8b03565
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Doped Carbon Materials as Metal-Free Catalyst for the Dechlorination of Trichloroethylene by Sulfide

Abstract: A new method for trichloroethylene (TCE) dechlorination is proposed using sulfide (HS − and S 2− ) as reductant under the mediation of nitrogen-doped carbon materials (NCMs). About 99% of the TCE was converted to acetylene after 200 h using this method. Dechlorination of TCE in the NCMs−sulfide system (NCSS) followed pseudo-first-order kinetics. Pyridinic N (N6) on surface of the NCMs appeared to play a critical role in NCSS as shown by the good linear relationship between the surface content of N6 and k obs .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 42 publications
4
27
0
Order By: Relevance
“…With the difference in pyrolysis temperature, heating time, preparation of raw materials, and other factors, the properties of biochar will differ, its functions will be more abundant, and its development potential is virtually unlimited [26][27][28][29]. In the pollutant treatment process, these carbon materials, including commercial carbon materials, biochar, and its modified materials, exhibit a wide range of effective applications for the treatment of halogenated hydrocarbons [30,31], benzene series [32,33], heavy metals [34,35], and other pollutants. As a matter of course, these series of carbon materials can be applied to the treatment of dyes, most of which feature adsorption and advanced oxidation [36,37], but few have been used as catalysts for the sulfide-based reduction of dyes.…”
Section: Introductionmentioning
confidence: 99%
“…With the difference in pyrolysis temperature, heating time, preparation of raw materials, and other factors, the properties of biochar will differ, its functions will be more abundant, and its development potential is virtually unlimited [26][27][28][29]. In the pollutant treatment process, these carbon materials, including commercial carbon materials, biochar, and its modified materials, exhibit a wide range of effective applications for the treatment of halogenated hydrocarbons [30,31], benzene series [32,33], heavy metals [34,35], and other pollutants. As a matter of course, these series of carbon materials can be applied to the treatment of dyes, most of which feature adsorption and advanced oxidation [36,37], but few have been used as catalysts for the sulfide-based reduction of dyes.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not able to conclude a consistent finding of contaminant dependence from currently available studies, for the reason that contrary results were reported even for the same contaminant, for example, nitroaromatic compounds mentioned before. Third, many other properties other than quinone moieties and graphitic regions were affecting the activity of carbon materials, including N elements (Ding et al, 2018;Liu et al, 2017), and affinities to different substrates. The extent of their influences may be small, but they can function with other properties synergistically to result in the diversity of catalytic performance.…”
Section: The Decisive Property For the Performance Of Carbon Materialsmentioning
confidence: 99%
“…Obviously, any reduction of a contaminant in the cathodic cell can confirm that the reaction of contaminants can-at least partially-arise from direct electron transfer through the carbon material, if not, the intermediates formed by the interaction of the carbon material with the reductant should be responsible for the reduction. This approach has been applied to investigate the degradation pathway for RDX, nitroglycerin (Xu et al, 2010), 3-bromonitrobenzene (Xu et al, 2015), DDT (Ding & Xu, 2016), TCE (Ding et al, 2018), and (di)chloroacetamides (Xu et al, 2020), with sulfide as a reductant. Among them, only nitroglycerin has been observed to decay in the cathodic cell, indicating the reduction of most contaminants in carbon-sulfide systems relies on the intermediates.…”
Section: Reduction Pathways In Carbonreductant Systemsmentioning
confidence: 99%
See 2 more Smart Citations